Empirical research of foreign direct investments efficiency in the European Union on the edge of pandemic outbreak. - Milan Džogan; Roman Lacko; Zuzana Hajduová (PLoS ONE)
The study focuses on the effects of the COVID-19 pandemic on the economy and foreign direct investments in the European Union countries. Using data envelopment analysis constant and variable returns to scale models, and the Malmquist productivity index, we measured the efficiency of economic resource utilization concerning foreign direct investments and gross domestic product. These efficiencies were assessed in 2019, before the full outbreak of COVID-19, and in 2020, when uncertainty and the consequences of the pandemic were most pronounced. Despite the challenges posed by the pandemic, the European Union displayed economic resilience in the first year, with no significant reduction in foreign direct investment efficiency. Lower-income European Union countries saw an increase in foreign direct investment efficiency, attributing this to positive changes in managerial efficiency. This suggests that decisions made by authorities positively impacted foreign direct investment flows in economically less developed European Union regions despite restrictive measures and market uncertainties.